Silica Sand Potency of Bukit Pelintung as Base Material of Solar Cell - Kausarian, Husnul; Umar, Mursyidah; Wiyono, Sugeng (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2013)
Bukit Pelintung is a part of the Pematang formation exposed at the surface. Bukit Pelintung has different lithology with the area surround it, where the area surround Bukit Pelintung consists of old and young superficial deposit with peat, clay and silt lithology. Bukit Pelintung is a part of the Pelintung village, subdistrictMedangKampai, Dumai city located in the northeastern city of Dumai. The total area of Bukit Pelintung is about 36km2. Silica sand in Bukit Pelintung associated with iron (Fe2O3) sand and alumina (Al2O3) sand and characterized by different colors of sand. Four-point location of the research area that has been conducted in Bukit Pelintung showed a high silica content. Laboratory test using the X-RF (X-Ray Fluorescence) method showed the compound silica (SiO2) has a high percentage above 95%.